2006
DOI: 10.1021/ja056166n
|View full text |Cite
|
Sign up to set email alerts
|

EPR−ENDOR of the Cu(I)NO Complex of Nitrite Reductase

Abstract: With limited reductant and nitrite under anaerobic conditions, copper-containing nitrite reductase (NiR) of Rhodobacter sphaeroides yielded endogenous NO and the Cu(I)NO derivative of NiR. (14)N- and (15)N-nitrite substrates gave rise to characteristic (14)NO and (15)NO EPR hyperfine features indicating NO involvement, and enrichment of NiR with (63)Cu isotope caused an EPR line shape change showing copper involvement. A markedly similar Cu(I)NONiR complex was made by anaerobically adding a little endogenous N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 35 publications
5
68
2
Order By: Relevance
“…A conundrum remained: Which Cu-NO species is produced in the enzymatic cycle (VI)? Whereas side-on NO is stabilized in crystal structures (22,23,25), spectroscopic and computational studies indicate that end-on NO is a physiological intermediate (37)(38)(39)(40). Although visualization of an end-on NO species with short lifetime has been difficult, time-resolved SFX may enable it (60,61).…”
mentioning
confidence: 99%
“…A conundrum remained: Which Cu-NO species is produced in the enzymatic cycle (VI)? Whereas side-on NO is stabilized in crystal structures (22,23,25), spectroscopic and computational studies indicate that end-on NO is a physiological intermediate (37)(38)(39)(40). Although visualization of an end-on NO species with short lifetime has been difficult, time-resolved SFX may enable it (60,61).…”
mentioning
confidence: 99%
“…Extensive theoretical work has previously examined the binding of NO to T2Cu in CuNiRs and overall has proposed that end-on binding should be energetically preferred over the side-on binding observed in the crystal structures. ENDOR/ EPR experimental work on Rhodobacter sphaeroides CuNiR also suggested an end-on mode in solution (Usov et al, 2006). Our data thus suggest either that CuNiR in room-temperature solution and CuNiR in the crystalline state produce different product geometries, which we consider to be unlikely, or that the theoretical studies have not yet fully represented the binding geometry in vivo.…”
Section: Insights Into the T2cu-no Complex In Cunirsmentioning
confidence: 69%
“…S2 in Supplementary Material), a fact that indicates that the features observed in the EPR signal cannot be attributed to interaction between the S = 1/2 radical species and the nuclear spin of the N atom of nitrite. The formation of copper(I)-nitrosyl adducts has been reported in a few copper complexes [45,46] and in the Nirs from A. faecalis S6 [41], R. sphaeroides [42], and A. cycloclastes [47]. The crystal structure of A. faecalis S6 Nir obtained by soaking ascorbate-reduced single crystals with NO-saturated buffer and that of as-isolated A. cycloclastes Nir with an endogenous NO ligand showed an unexpected side-on coordination of NO to Cu(I), in contrast to the end-on configuration adopted by NO in copper inorganic complexes [46].…”
Section: Epr Characterization Of the Copper Centersmentioning
confidence: 94%
“…This interpretation was based on EPR simulations assuming typical g-and A-values for a T2 site plus hyperfine coupling to four N-nuclei at g ⊥ , three from the coordinating histidines and one from the NO, and on X-ray data which showed a side-on NO coordinated to Cu [41]. In contrast, other authors, on the basis of EPR, ENDOR (Electron-Nuclear Double Resonance), and DFT (Density Functional Theory) calculations in R. sphaeroides NiR [42,43], concluded that the species generated in solution of ascorbate-reduced Nir with excess NO corresponds to a Cu II -NO 2 − species.…”
Section: Epr Characterization Of the Copper Centersmentioning
confidence: 97%